Investment-based santripreneur training in the Islamic capital market - Bastomi, Mohamad; Salim, Muhammad Agus (Universitas Muhammadiyah Magelang, 2021)
The majority of Anwarul Huda Islamic boarding school's students (Santri) are students from various universities in Malang City who have limited time, energy, and capital if they want to pursue entrepreneurship. This causes the Anwarul Huda Islamic boarding school students to lack the skills and experience to do business. This service aims to introduce and train students in investing in the Islamic capital market. The methods used in this service were counseling, demonstration, tiered training, and mentoring. Community service was able to increase students' understanding of investment opportunities in the capital market; santri have a security account; and able to simulate the trading process.